2021
DOI: 10.1007/s12517-020-06350-2
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Fusarium head blight in wheat ears using vertical angle-based reflectance spectroscopy

Abstract: Fusarium head blight (FHB) is a major disease that negatively affects wheat yield in China. Given that conventional reflectance spectroscopy measurements are perpendicular to crop canopy, the identification of FHB in wheat ears with the spectral data from the vertical angle can provide the possibility for large-scale monitoring. In this study, multi-features were selected and constructed to realize the identification of FHB in wheat ears from the vertical angle, and the influence of leafy and leafless samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Therefore, scab attracts attention because of its wid tribution and severe impact on grain quality. However, the bibliometric revie yses of scab under ARS demand the significant attention of the scientific com hough the recent focus has been devoted to scab [40,[42][43][44][45] and other plan conclusive methodology at a large scale is still highly needed. * LLR abbreviation of log-likelihood ratio used to achieve the optimal results with maximum coverage and uniqueness.…”
Section: Description Of Cluster Analysismentioning
confidence: 99%
“…Therefore, scab attracts attention because of its wid tribution and severe impact on grain quality. However, the bibliometric revie yses of scab under ARS demand the significant attention of the scientific com hough the recent focus has been devoted to scab [40,[42][43][44][45] and other plan conclusive methodology at a large scale is still highly needed. * LLR abbreviation of log-likelihood ratio used to achieve the optimal results with maximum coverage and uniqueness.…”
Section: Description Of Cluster Analysismentioning
confidence: 99%
“…Canopy reflectance can be used to identify specific stressors and diseases by recording canopy reflectance at multiple time points over an extended period. To date, the reflectance-based examination of FHB infected wheat canopy has not been practiced while a number of studies have examined the field wheat targeting the spikes only, employing diverse types of sensors [8,49].…”
Section: Estimation Of Disease Severity Using Conventional and Newly ...mentioning
confidence: 99%
“…Meanwhile, 846 nm characterizes the structural variation in the nearinfrared region of canopy reflectance. However, the role of water can also be speculated upon, as blighted spikes typically contain less water than healthy spikes [8,9,49,53]. The authors of [25] identified a similar waveband 866 nm for rice leaf blast.…”
Section: Interpretation Of Selected Spectral Bands and Vegetation Ind...mentioning
confidence: 99%
See 1 more Smart Citation
“…Conventional detection methods, such as sampling analysis, are mostly performed by experts and experienced farmers in the field. This approach cannot meet the requirements for monitoring large areas, and it is time-consuming and laborious [5,6]. Hyperspectral remote sensing technology can quickly monitor crop diseases and is suitable for largescale applications [7,8].…”
Section: Introductionmentioning
confidence: 99%